2020
DOI: 10.1080/03019233.2020.1823199
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tuyere failure categories in 5800 m3 blast furnace

Abstract: The tuyere is an important item of equipment for a blast furnace. However, the tuyere life of the large blast furnace can be quite short. The failure of tuyere will seriously affect the production of a blast furnace. So, it is of great significance to carry out experimental research on any damaged tuyere with a view to extending its service life. The damaged tuyere from a 5800m 3 blast furnace in China was analyzed by SEM, EDS and optical microscope. According to the results of microscopic phase analysis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…q in ¼ 0.005281 Â P 1.156 Â ð1.8 Â ðT À T sat ÞÞ 2.40 P 0.0234 (6) The heat transfer prior to the inception of boiling is given by the Dittus-Bolter equation ( 4) and the corresponding heat flux by Equation (5). The temperature at which heat flux at the inception of nucleate boiling, Equation ( 6), exceeds the heat flux given by Equation ( 5), is the temperature at which nucleate boiling initiates.…”
Section: Prediction Of Onset Of Boilingmentioning
confidence: 99%
See 1 more Smart Citation
“…q in ¼ 0.005281 Â P 1.156 Â ð1.8 Â ðT À T sat ÞÞ 2.40 P 0.0234 (6) The heat transfer prior to the inception of boiling is given by the Dittus-Bolter equation ( 4) and the corresponding heat flux by Equation (5). The temperature at which heat flux at the inception of nucleate boiling, Equation ( 6), exceeds the heat flux given by Equation ( 5), is the temperature at which nucleate boiling initiates.…”
Section: Prediction Of Onset Of Boilingmentioning
confidence: 99%
“…Gao et al have explained three categories of tuyere failure, erosion and melting, bending, and crack propagation. [ 6 ] Out of these, the mechanism of erosion and the subsequent failure have been elaborated by Gao et al [ 7 ] The erosion pattern of the tuyere has also been exposed by comparing the used tuyeres with the original model by Chatterjee et al [ 8 ] It was found that the top part of the tuyere nose is the most vulnerable.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have conducted extensive research on how to improve the life of blast furnace tuyeres. Gao et al [ 7 ] analyzed the erosion mechanism of tuyeres in large blast furnaces by observing samples from different parts of damaged tuyeres in a 5800 m 3 blast furnace in China. They found that the erosion types of the tuyeres are very complex and can be classified into four categories: melting erosion, point erosion, cracking, and deformation of the tuyere.…”
Section: Introductionmentioning
confidence: 99%
“…Its working environment is extremely harsh. On one hand, the tuyere small sleeve end is repeatedly bonded and peeled off by the high-temperature slag and iron, causing the melting and erosion failure of the tuyere small sleeve end [2][3][4]. On the other hand, the hot air and fuel supplied by the tuyere small sleeve to the furnace undergo violent combustion under high-temperature and high-pressure conditions [5], leading to the tuyere small sleeve end bearing a huge thermal load.…”
Section: Introductionmentioning
confidence: 99%